Comparison of non-covalent binding interactions between three whey proteins and chlorogenic acid: Spectroscopic analysis and molecular docking. (June 2021) - Zhang, Yuanyuan; Lu, Yingcong; Yang, Yang; Li, Siyao; Wang, Ce; Wang, Cuina; Zhang, Tiehua
Abstract: Non-covalent binding interactions between three whey proteins β-lactoglobulin (β-Lg), α-lactalbumin (α-La) and bovine serum albumin (BSA) with chlorogenic acid (CA) were investigated using spectroscopic analysis and molecular docking. Fluorescence study showed that CA quenched the fluorescence of three whey proteins through static mode. The binding number was equal to 1 for three proteins and binding affinity in declined order was: α-La > β-Lg > BSA. Thermodynamic parameters revealed contribution of hydrophobic force in three systems. Fluorescence resonance energy transfer (FRET) measurements indicated that energy transfer occurs between three proteins and CA in probability of α-La > BSA > β-Lg. Variation in surface charge indicated the involvement of electrostatic interaction. Surface hydrophobicity (H0 ) were declined with decrease degree of α-La > β-Lg > BSA. α-La and β-Lg were unfolded with more flexible structure while BSA skeleton was more compact after interacting with CA. Modeling study revealed that the most likely binding sites for the three proteins were outer surface, cleft and subdomain I for β-Lg, α-La and BSA respectively. Docking results also suggested the contribution of hydrophobic interaction and hydrogen bond (β-Lg, α-La) for formation of molecular nano complexes between whey proteins and CA.